Revealing Short-Term Precursors of the Strong M > 7 Earthquakes in Southern California From the Simulated Stress–Strain State Patterns Exploiting Geomechanical Model and Seismic Catalog Data - Bondur, Valery G.; Gokhberg, Mikhail B.; Garagash, Igor A.; Alekseev, Dmitry A. (Frontiers in Earth Science, 2020)
Since 2009, the stress–strain state (SS) of the earth’s crust in Southern California region is being monitored through geomechanical modeling, taking into account the ongoing seismicity with magnitudes M > 1. Every new earthquake is assumed to cause a new defect in the earth’s crust, leading to redistribution in the SS. With half-monthly SS updates, we found that the two strong earthquakes with M ∼ 7 that occurred in the area in 2010 and 2019 had been preceded by anomalies in the strength parameter D (indicating how close the rock is to its ultimate strength), which had emerged a few weeks to months before the main shock at a distance of 10–30 km from the future epicenter. Over the course of monitoring (nearly a decade), this approach has neither produced false alarms nor missed events with M > 7 falling within the modeling area.